INDONESIA DALAM BELITAN KEJAHATAN LINTAS NEGARA : Kasus Perdagangan Orang pada Pekerja Migran - Pudjiastuti, Tri Nuke (Jurnal Penelitian Politik, 2011)
Rapid growth oftransnational crimes are considered as one serious threat to global security particularly in Indonesia Indonesia stillfaces complex problems in many issues oftransnational crimes In this case traffickingin persons is one ofcurrent issues which related with international migration Many factors contribute to the complexity and growingfast Even though Indonesia plays an active role in the international bilateral and regionalcooperation in the prevention and handling of transnational crimes Indonesian foreign affairs still faces manydifficulties to reduce that trafficking in persons